Integrating geospatial technologies into the right-of-way data-management process - Hancock, Kathleen L.; National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board; Virginia Polytechnic Institute. Center for Geospatial Information Technology (Washington, DC Transportation Research Board, 2006)
"This digest presents the key findings from NCHRP Project 8-55, "Integrating Geospatial Technologies into the Right-of-Way Data-Management Process," conducted by Kathleen L. Hancock , Center for Geospatial Information Technology, Virginia Polytechnic Institute and State University, Alexandria, Virginia"--P. [1].
Caption title.
"December 2006."
Includes bibliographical references (p. 13).
Also available online via the Transportation Research Board publications web page.
Keywords: Right of way -- United States -- Data processing; Geospatial data -- United States